THE INFLUENCE OF SOCIO-ECONOMIC FACTORS ON DISABILITY STATUS AMONG OLDER ADULTS IN INDONESIA - Martha Budi Wardani; Febri Wicaksono (Universitas Airlangga, 2026)
Indonesia is currently experiencing population aging, characterized by an older adult population that exceeds 10 percent of the total population. The proprotion of older adults continues to increase each year and is expected to raise new challenges, particularly the rising prevalence of disability among older adults. Government health policies should address this issue and reduce the risk of disability among older adults. However, according to the BPS-Statistics Indonesia data between 2010 and 2022, the prevalence of disability among older adults has generally increased. This increase has the potential to place a greater burden on families, communities, and the state. Therefore, this study aimed to identify the socioeconomic factors associated with disability status among older adults in Indonesia. The study used data from the 2023 Indonesia’s National Socio-Economic Survey (SUSENAS), comprising a sample of 129,individuals aged 60 years and above. Binary logistic regression was employed for data analysis. The results showed that welfare level, age, gender, marital status, place of residence, and education level were significantly associated with disability status among older adults. These findings are expected to support preventive measures and early intervention efforts and assist the government ino developing effective policies and programs to promote healthy aging and reduce the prevalence of disability among older adults in the future.